De Novo Assembly of Transcriptome and Development of Novel EST-SSR Markers in Rhododendron rex Lévl. through Illumina Sequencing - Zhang, Yue; Zhang, Xue; Wang, Yue-Hua; Shen, Shi-Kang (Frontiers in Plant Science, 2017)
Transcriptome sequences generated by next-generation sequencing technologies can be utilized to rapidly detect and characterize a large number of gene-based microsatellites from different plants. Rhododendron rex Lévl. is a perennial woody species from the family Ericaceae and an endangered plant with high ornamental value endemic to Southwestern China. Nevertheless, the genetic and genomic information of R. rex remain unknown. In this study, we performed transcriptome sequencing for R. rex leaf samples, and generated large transcript sequences for functional characterization and development gene-associated SSR markers. A total of 164,242 unigenes were assembled and 115,089 (70.07%) unigenes were successfully annotated in public databases. In addition, a total of 15,314 potential EST-SSRs were identified, and the frequency of SSRs in the R. rex unigenes was 9.32%, with an average of one EST-SSR per 5.65 kb. The most abundant type was repeated di-nucleotide (54.63%), followed by mono- (26.03%) and tri-nucleotide (18.51%) repeats. Based on the SSR-containing sequence, 100 primer pairs were randomly selected and synthesized and used for assessment of the polymorphism. Thirty-six primer pairs were polymorphic and revealed polymorphism among 20 individuals from four R. rex populations. A total of 197 alleles were identified, with an average of 5.472 alleles per locus. The Polymorphism Information Content ranged from 0.154 to 0.870, with a mean of 0.482. The newly developed EST-SSR markers exhibited high transferability (58.33%–83.33%) among the six subgenera. Thus, these novel EST-SSR markers developed would provide valuable sequence resources for population structure, genetic diversity analysis, and genetic resource assessments of R. rex and its related species.